PENGARUH KOMUNIKASI KESEHATAN RSUD BONTANG MELALUI INSTAGRAM @RSUDBONTANG TERHADAP PENERIMAAN INFORMASI AKURAT MASYARAKAT - Putri, Helmania; Hairunnisa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Over time, people's needs in using social media include information about health to anticipate and take the first step in dealing with their illness. Health communication itself is one way to convey messages that cover health issues. However, there are shortcomings of social media that are felt to pay less attention to technical matters in conveying health information and this is felt by the Instagram manager himself. The Instagram @rsudbontang that people rely on to get health information about health entertainment and health services. Therefore, to find out the Effect of Health Communication carried out by the Bontang Regional General Hospital (RSUD) on Public Information Reception. This research is of the Quantitative type to obtain data. Data collection techniques using Purposive Sampling and using the Slovin formula which resulted in 97 people as respondents. The results of this study indicate that Health Communication carried out by the Bontang Regional General Hospital (RSUD) through Instagram @rsudbontang as a medium has an influence of 64% on the receipt of accurate information obtained by the community, while the remaining 36% is influenced by other factors not included by researchers. In the results of the t test, the calculated t value of 13.050 is greater than the t-table value of 1.661, which means that the Ha hypothesis is accepted that Health Communication carried out by the Regional General Hospital (RSUD) Bontang through Instagram on Receiving Accurate Information from the community.